Preliminar evaluation of inbred Unes from tbe cross between Zea mays L. x Zea diploperennis I. (Semiárida, 2020)
In Argentina, as in most of the countries, do not exist cultivars o hybrids of corn destined exclusively to forage production, and hybrids selected for grain production are used for such purpose. Forage corns differ from grain purpose corns in the development of air part, grain filled, maintenance of the green plant harvest, digestible dry matter content and animal intake. Corn forage used as silage is considered an energetic food and its nutritious value depends on its digestibility. A criterion used for selection is in vitro digestibility of the dried matter of leaves and stems. With the purpose to a preliminary evaluation of corn with introgression of wild genes, is analized botanic components of the plant, the digestibility in vitro of total dry matter and the digestible dry matter of whole plant and leat and stem in seven linbred lines (S3 ) of corn. The experimental Iines and the hybrid showed similar total dry matter digestibility in vitro value. The higher dry matter production of the experimental Iines incresed the digestible dry matter production of the whole plants, leaves and stems. Quantity and digestibility of stem were highly associated with the dry matter nutritious parameters analyzed.
Keywords: Zea mays; Zea diploperennis; S3 Iines; forage maize; dry matter digestible production